GUGATAN WANPRESTASI TERHADAP TUNGGAKAN PEMBAYARAN BARANG FARMASI KEPADA PERUSAHAAB DISTRIBUTOR FARMASI (Studi Putusan Nomor 15/Pdt.Gs/2022/PN.Tjk) - Risti Dwi Ramasari; Intan Nurina; Reza Uyundoya (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Default comes from the Dutch language "wanprestastie", which means non-fulfillment of achievements or obligations that have been assigned to certain parties in an engagement, both agreements born of an agreement or agreements arising from a law. According to the Legal Dictionary, default means negligence, negligence, default, not fulfilling its obligations in the agreement. Legal Consequences of Default Against Arrears in Payment of Pharmaceutical Goods to Pharmaceutical Distributor Companies in Decision Number 15/Pdt.Gs/2022/ PN. Tjk is that Muhamad Sutedjo must pay his payment obligations to the Plaintiff Rp. 113,424,307.50 (one hundred thirteen million four hundred twenty four thousand three hundred seven rupiah and fifty cents). And plus paying interest of 6% (six percent) per year from IDR 113,424,307.50 (one hundred thirteen million four hundred twenty four thousand three hundred seven rupiah fifty cents) starting from June 14, 2022 (due date of subpoena second from the Plaintiff) until this decision was read out and the Basis for consideration of the Judge in imposing a decision on default in the arrears of payment for pharmaceutical goods to a Pharmaceutical Distributor Company in Decision Number 15/Pdt.Gs/2022/PN.Tjk is based on the provisions in Article 1320 KUH Civil requirements for the validity of an agreement, Article 1925 of the Civil Code Jo Article 163 HIR/283 RBg because the Defendant did not dispute, Supreme Court Jurisprudence Number 063 K/PDT/1987 concerning Addition of interest of 6% of the principal amount of the loan and Article 18 paragraph (1) Perma Number 4 of 2019 concerning Amendments to Perma Number 2 of 2015 concerning Procedures for Settlement of Simple Claims.